Management of uncertsinty in the safety : - evaluation of individual risk - Aagaard, Pierre E. (Proceedings from the Annual Transport Conference at Aalborg University, 1997)
Risk models used to evaluate whether a transport activity operates at a tolerable safety level or not often contain uncertain elements. An uncertain element could be the values of model parameters which are estimated on the basis of limited accident data. In order to make a more balanced safety evaluation, uncertain elements in the used risk model ought to be taken into account. This paper address how uncertainty in the accident frequency and accident outcome can be accounted for in the evaluation of individual risk posed by a public transport activity. The accident outcome is in the paper represented by the mean number of fatalities per fatal accident. The uncertainty in the parameters are represented by Bayesian probability distributions. It is analysed how uncertainty in the fatal accident frequency and the mean number of fatalities may affect the decision whether the individual risk posed by the transport activity is tolerable or not.